2019
DOI: 10.1007/s11051-018-4442-9
|View full text |Cite
|
Sign up to set email alerts
|

Particle atomic layer deposition

Abstract: The functionalization of fine primary particles by atomic layer deposition (particle ALD) provides for nearly perfect nanothick films to be deposited conformally on both external and internal particle surfaces, including nanoparticle surfaces. Film thickness is easily controlled from several angstroms to nanometers by the number of self-limiting surface reactions that are carried out sequentially. Films can be continuous or semi-continuous. This review starts with a short early history of particle ALD. The dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 117 publications
(227 reference statements)
0
56
0
1
Order By: Relevance
“…Trimethylaluminum oxide (ALD precursor for Al 2 O 3 deposition) does not bind well on the Au surface, so probably a deposition of 1–5 nm of Al 2 O 3 results in some pinholes on the Au nanoislands that penetrate through the entire layer. 64 The addition of thicker layers of ALD Al 2 O 3 before current is eliminated has also been observed in halide perovskite solar cells recently. 65 The dependence of the photocurrent on the thickness of the insulating layer provides additional verification that the oxidation of Mn 2+ to MnO x is the result of a hot hole rather than a purely thermal or chemical reaction mechanism.…”
Section: Resultsmentioning
confidence: 91%
“…Trimethylaluminum oxide (ALD precursor for Al 2 O 3 deposition) does not bind well on the Au surface, so probably a deposition of 1–5 nm of Al 2 O 3 results in some pinholes on the Au nanoislands that penetrate through the entire layer. 64 The addition of thicker layers of ALD Al 2 O 3 before current is eliminated has also been observed in halide perovskite solar cells recently. 65 The dependence of the photocurrent on the thickness of the insulating layer provides additional verification that the oxidation of Mn 2+ to MnO x is the result of a hot hole rather than a purely thermal or chemical reaction mechanism.…”
Section: Resultsmentioning
confidence: 91%
“…Generally, the independence of the loading from temperature and amount of dosed precursor is taken as proof that the conditions for ALD are fulfilled and the process operates within the ALD window. [53][54][55][56] Furthermore, Libera et al, 57 reported that the deposition of Zn via ALD on SiO 2 particles at temperatures above 150 °C yields metallic Zn and ZnO simultaneously. The presence of metallic Zn is reported as an indication of a chemical vapour deposition (CVD) process occurring in parallel.…”
Section: Discussionmentioning
confidence: 99%
“…The complete encapsulation of particles is a major category that utilizes ALD advantages of conformal and uniform growth to deposit pinhole-free films of critical thickness at nanometer scale [30]. The conformal coating is mainly used to protect the coated materials and increase stability while keeping the original properties of the primary particles.…”
Section: Conformal Coating On Particlesmentioning
confidence: 99%